Dynamic modulation of proximity-induced enzyme activity using supramolecular polymers. Issue 43 (22nd April 2020) - Magdalena Estirado, Eva; Rosier, Bas J. H. M.; de Greef, Tom F. A.; Brunsveld, Luc
Abstract : Synthetic supramolecular polymers are used as dynamic nanoscaffolds for the activation of the apoptotic signalling enzyme caspase-9. Abstract : Synthetic supramolecular polymers are used as dynamic nanoscaffolds for the activation of the apoptotic signalling enzyme caspase-9. Recruitment of caspase-9 to the nanoscaffold results in an increase in enzymatic activity due to enhanced proximity, with a bell-shaped response as a function of nanoscaffold concentration. The modularity of the system allows for dynamic regulation of enzyme activity through variation of the recruitment-motif density along the supramolecular polymer.